On the Stability of the Maximum Term of the Entire Dirichlet Series - Skaskiv, O. B.; Trakalo, O. M. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We establish necessary and sufficient conditions for logarithms of the maximal terms of the entire Dirichlet series F(z) = ^+∞_n=0a_n e^zλ_n and A(z) = ^+∞_n=0a_n b_n e^zλ_n to be asymptotically equivalent as Re z → +∞ outside some set of finite measure.